Sejarah Penerbitan Jurnal Sejarah Di Malaysia 1846-1966: Satu Tinjauan Awal - Tiew, W.S. (Jabatan Sejarah Universiti Malaya, 2000)
This article attempts to identify and compile a list of the earliest Malaysian historical journals. The study found that the earliest historical journal is Journal of the Indian Archipelago and Eastern Asia published in 1847 by James Richardson Logan, a well-known lawyer and journalist from the Straits Settlement, British Malaya. On the whole, between 1847 till 1966, as many as ten Malaysian historical journals were published by various history-related institutions, associations and individuals. Some of these publications are still actively publishing their journal while others had ceased issuing their journals.